School Counselor Management in Handling Bullying Cases in Students - Hengki Yandri; Neviyarni Suhaili; Riska Ahmad (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2023)
Bullying cases between students at school are still a frequent problem in various countries, including Indonesia. Thus, the role of Bk teachers in schools is crucial in solving the problem of bullying in schools. The purpose of this study is to reveal how school counselors carry out management in solving bullying cases in schools. This research uses an Intrinsic Case Study approach with BK teacher research subjects who have succeeded in solving bullying cases in their schools. Data is revealed by interviews, documentation, and Forum Group Discussion (FGD) then the data that has been collected is analyzed through the following stages: 1) category collection; 2) direct interpretation; 3) form patterns and seek compatibility between two or more categories; and 4) develop natural generalizations. The results revealed that in solving bullying cases in schools, BK teachers use a personal approach (individual counseling and advocacy), create bullying prevention programs, peer counselor training, and collaborate with principals, vice principals for student affairs and homeroom teachers and parents in developing anti-bullying programs at school